The Activity of an Educational Field by Means of Assisting in the Development the Speed Movement and Shooting Skill of Football For Youth - Husam Kadhim Jawad; Asaad Hussein Abd Alrazaq (Institute of Medico-legal Publications Pvt Ltd, 2021)
The importance of the research lies in preparing an educational field in developing motor speed and footballscoring skill for cubs, depending on the stock of motor abilities and skills that were learned in a previousperiod and which are prerequisites for motor learning and achieving good technical performance that securesa level of performance. the researchers decided to prepare an educational field by means of assisting in thedevelopment of kinematic speed and football scoring skill for cubs in order to reach the desired and intendedachievement. The research objective : Preparing an educational field with assistive means to develop motorspeed and soccer scoring skill for young players. The researchers used the experimental approach in solvingthe research problem, and on the research community, the research community was identified with youngplayers of ages (13-14) years for the football school to foster the sporting talent in football for the Kothadistrict / Babil governorate, whose number is (22) players, and they were divided equally by the method,simple randomness. As for the most important conclusions, they were: The educational field contributed bymeans of assisting in the development of motor velocity and the skill of scoring football for young players.